1985
DOI: 10.1111/j.1751-1097.1985.tb01597.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOPHYSICAL and PHOTOCHEMICAL PROPERTIES OF COUMARIN DYES IN AMPHIPHILIC MEDIA

Abstract: Abstract— Photophysical properties of coumarin dyes solubilized in aqueous detergent solutions have been investigated including measurement of absorption and fluorescence emission maxima, and fluorescence quantum yields. Use of coumarin 4 as a fluorescence probe of sodium dodecyl sulfate (SDS) and cetyltrimethylammonium bromide (CTAB) solutions led to the conclusion that the sites for dye incorporation in micelles are significantly hydrogen‐bonded (hydrated). The inhibition of photochemical decomposition for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…The RFI value of 1f, with the strongest electron-withdrawing nitro group, was comparable with that of 1b, with an electron-donating methyl group. This prominent decrease in 1f may be attributed to the nonemissive twisted ICT (TICT) excited state, [39][40][41][42][43] where push-pull p-electron systems between a methoxyl group at the 6-position and a nitro group at the 3-position in a molecule must be fully separated in polar solvent such as acetonitrile. Rettig and Klock reported that the very weak fluorescence of 6-aminocoumarin with a stronger electron-donating amino group than the methoxyl group was attributed to this TICT between the amino group and coumarin ring.…”
Section: Resultsmentioning
confidence: 99%
“…The RFI value of 1f, with the strongest electron-withdrawing nitro group, was comparable with that of 1b, with an electron-donating methyl group. This prominent decrease in 1f may be attributed to the nonemissive twisted ICT (TICT) excited state, [39][40][41][42][43] where push-pull p-electron systems between a methoxyl group at the 6-position and a nitro group at the 3-position in a molecule must be fully separated in polar solvent such as acetonitrile. Rettig and Klock reported that the very weak fluorescence of 6-aminocoumarin with a stronger electron-donating amino group than the methoxyl group was attributed to this TICT between the amino group and coumarin ring.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Aminocoumarin dyes have also been used to study solvation dynamics in zeolites, micelles, and reversed micelles. 8,9 The reason for such a wide application range of the aminocoumarin dyes is due to the fact that on optical excitation they undergo an intramolecular charge transfer (ICT) from the electron-donating amino group to the electron-withdrawing carbonyl group of the coumarin ring.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, the following finding is noteworthy. In pursuit of increasing the solubility of coumarins in water, the authors have found that the addition of the pertinent detergents not merely increases the solubility of some of these dyes by orders of magnitude but also causes spectral shifts in the coumarins fluorescence (up to 30 nm), enhance their fluorescence quantum yield and reluctance towards photodegradation. In the context of the present work, noteworthy is also more apposite way to modify the spectral characteristics of organic dyes in both liquid and solid environments, which pertains to using the structured media …”
Section: Introductionmentioning
confidence: 99%